Pivoting in the pandemic: a qualitative study of child and adolescent psychiatrists in the times of COVID-19 - Madeline DiGiovanni; Indigo Weller; Andrés Martin (BMC, 2021)
Abstract Objectives We examined the personal and professional impacts of the COVID-19 pandemic on the development, practice, and shifting values of child and adolescent psychiatrists (CAP), in order to inform how the field may move forward post-pandemic. Methods We conducted individual semi-structured interviews of child and adolescent psychiatrists (n = 24) practicing in the United States. Participants were selected as a diverse purposive sample of active members of the American Academy of Child and Adolescent Psychiatry (AACAP). We analyzed anonymized transcripts through iterative coding using thematic analysis aided by NVivo software. Results We identified three main thematic domains within participants' response to the pandemic, which have engendered a reevaluation of and a recommitment to the aims of each clinician and the field of CAP more broadly. These domains, paired with representative questions, include: (1) Unsettling, or "who have we been?" (identifying discontents such as daily inefficiencies and intraprofessional loss of trust); (2) Adaptation, or "who are we now?" (exploring affordances and limitations of virtual work, and the evolution of personal and professional identity); and (3) Reimagination, or "who will we become?" (renewing a commitment to psychiatry as advocacy). Even as we identified a collective agreement toward the need for implementing change, just what needs to change, and how that change will be realized, remain contested. Conclusion These three thematic domains, augmented by a national confrontation with race and equity, have engendered a field-wide reckoning with known inequities. They have reinvigorated collective responses and calls to action. The divergent mindsets to change and leadership have provided an aperture for what values and practices the field might instill in its next generation of practitioners.